Hydroalcoholic extract and seed of Foeniculum vulgare improve folliculogenesis and total antioxidant capacity level in F1 female mice offspring - Fahimeh Pourjafari; Tahereh Haghpanah; Seyed Noreddin Nematollahi-Mahani; Fariba Pourjafari; Massood Ezzatabadipour (BMC, 2020)
Abstract Background Foeniculum vulgare (fennel) is traditionally suggested for the fertility improvement in Iranian lore due to its antioxidant and phytoestrogen compounds. The present study aimed to investigate the effects of fennel seed and its hydroalcoholic extract on the serum total antioxidant capacity (TAC) and folliculogenesis in offspring exposed to either of the treatments in utero and 56 days after birth (PND 56). Methods Pregnant NMRI mice were randomly divided into 5 groups of 7: extract-treated groups received 500 and 1000 mg/kg/day fennel extract (FE), seed-treated groups received 500 and 1000 mg/kg/day fennel seed (FS), and the control group (CTL) received no treatment. The treatments started from pregnancy day 1 and continued until PND 56. Body and right ovary weights and ovary dimensions were recorded. Hematoxylin and eosin stained ovary sections were prepared to calculate the proportion of different follicles. The level of TAC in the serums was also measured by fluorescence recovery after photo bleaching. Results A marked rise in the body and ovary weights of treated mice was observed compared to the CTL group. The mean number of primordial, primary, pre-antral, and pre-ovulatory follicles as well as corpus luteum size in the treated offspring was significantly higher compared to those of CTL offspring. The atretic follicle number was nonsignificantly lower in either of the treatment groups compared with that in the CTL. However, treatment of animals with 500 mg/kg FE showed a more pronounced effect. Animals in FS500, FE500 and FE1000 groups had a significantly higher level of serum TAC compared to the CTL group. Conclusions Fennel extract and seed administration in pregnancy and lactation period improve offspring's folliculogenesis. Higher level of TAC in the serum of offspring might have positively altered the folliculogenesis milieu.